Annual review of the sociology of religion. - Giordan, Giuseppe. (Annual Review of the Sociology of Religion, 2010)
The purpose of the Annual Review of the Sociology of Religion (ARSR) is to investigate the "new" role of religion in the contemporary world, which is characterized by cultural pluralism and religious individualism. It is the aim of the ARSR to combine different methods within the social scientific study of religion. The ARSR employs an interdisciplinary and comparative approach at an international level, to describe and interpret the complexity of religious phenomena within different geopolitical situations, highlighting similarities and discontinuities. Dealing with a single theme in each volume, the ARSR intends to tackle the relationship between the practices and the dynamics of everyday life and the different religions and spiritualities, within the framework of the post-secular society. This volume presents the religious and spiritual life of the young: an ever new and complex world which highlights the changes that are happening in the field of religion in general. With an outlook which is opened to various international contexts, its chapters offer a picture of the current situation between religion and the young, suggesting possible future trends.